(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
In today’s highly competitive business environment, information is the most important resource for all organizations, whether in the public or private sector. In most cases, this information is found in paper documents. Information capture systems (scanning, indexing) represent the first step in information management, allowing documents to be converted from a physical to an electronic format, as well as extracting the required information from them through digital archiving. We also record our personal experiences and life events digitally on computers, phones, and other electronic devices, in the form of documents, emails, images, social media, and audio/video files. So, here digitization and digital archiving are very important? Digitization and digital archiving, as an information security system, helps you to better manage personal information and records in digital repositories in an effective and secure way. It is about how you manage information and how you can make the most of it in an effective way that benefits you and your organization. Digital archiving of documents is one of the main drivers of economic transformation, as information analysis allows you to benefit from making better decisions, which is essential for any organization regardless of its size, type, or complexity. The development of technology and electronic communication systems in our lives has made it necessary to adopt them as a solution to the old problems that organizations face in their work. The difficulty of storing paper and keeping it safe from damage, despite the urgent need to return to it at times, led to the invention of a way to invest this technology in storing documents and information electronically. This resulted in the emergence of what is called digital archiving. Digital archiving is a necessity for website owners and businesses, as it is safe and secure in storing and retrieving all the required electronic data and files over the long term. The process of digital archiving works to index electronic documents and files, and keep them until they are needed. It organizes this data and provides a copy of the original for use in research, auditing, and legal purposes. The importance of digital archiving can be summarized in the following points: Quick access to the required information compared to the traditional archive method. No need to return to the paper archive and search through piles of papers. The ability to keep a huge amount of information that paper archiving cannot sometimes store. Reducing the number of employees (hidden unemployment) and tools, thus reducing the financial cost of companies. Facilitating the process of information exchange and sharing with others. Dispensing with unnecessary data. Developing the efficiency and quality of work using modern technologies. No need for large spaces in offices and institutions, and utilizing this space for more useful work. Conserving the environment by reducing waste and saving paper. Digital archiving can also store a large number of data and information that is difficult to store in the traditional archive as it is an effective and scalable method. Digital archiving plays an important role in meeting regulatory requirements through the use of technologies. The data stored is not subject to change or modification. Through digital archiving, you can find the required information regardless of its size. In addition to providing security means for information by identifying the people who can access it with the ability for more than one user to enter at the same time. Digital archiving also features ease of use remotely, the ability to meet the needs of the organization, and at the same time reduces the risks that the organization may face during work. In addition to its ability to restore damaged data, the ability to export data and save incoming faxes and types of emails, and the ease of handling different types of files. Therefore, the emergence of modern information technologies has necessitated a re-examination of the traditional concepts related to the archive and the processing of its contents of documents and dealing with them. The digital archive has emerged in all its technological dimensions, and it has taken on great importance due to its close association with the contemporary digital environment, going beyond the idea of digitization and electronic archiving of the traditional paper archive, to electronic practice in a purely digital environment. There are institutions that produce, store, and retrieve their archives in a purely electronic way in unprecedented conditions traditionally. Additional notes: I have tried to preserve the meaning of the original text as much as possible while making it grammatically correct and fluent in English. I have also added some clarifications and explanations where necessary to make the text easier to understand for an English-speaking audience. I have used the term "digital archiving" throughout the translation, as this is the most common term used in English to refer to this concept.